2021
DOI: 10.1038/s41398-021-01335-5
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and deliberate creative cognition during and after psilocybin exposure

Abstract: Creativity is an essential cognitive ability linked to all areas of our everyday functioning. Thus, finding a way to enhance it is of broad interest. A large number of anecdotal reports suggest that the consumption of psychedelic drugs can enhance creative thinking; however, scientific evidence is lacking. Following a double-blind, placebo-controlled, parallel-group design, we demonstrated that psilocybin (0.17 mg/kg) induced a time- and construct-related differentiation of effects on creative thinking. Acutel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(104 citation statements)
references
References 109 publications
(185 reference statements)
5
98
0
1
Order By: Relevance
“…Current findings are congruent with previous studies indicating positive yet limited effects of high doses of psychedelics on divergent thinking (Mason et al, 2021;Mason et al, 2019;). For instance, Zegans and colleagues (1967) conducted a placebo-controlled study with a low dose of LSD and observed that participants in the LSD condition showed more original responses as compared to participants in the placebo condition.…”
Section: Previous Studiessupporting
confidence: 92%
See 4 more Smart Citations
“…Current findings are congruent with previous studies indicating positive yet limited effects of high doses of psychedelics on divergent thinking (Mason et al, 2021;Mason et al, 2019;). For instance, Zegans and colleagues (1967) conducted a placebo-controlled study with a low dose of LSD and observed that participants in the LSD condition showed more original responses as compared to participants in the placebo condition.…”
Section: Previous Studiessupporting
confidence: 92%
“…For instance, showed that higher-order inhibitory performance is impaired under moderate doses (100µg) LSD and the inhibition deficits positively correlated with the level of visual hallucinations. Similarly, a recent study by Mason et al (2021) showed that acute effects of moderate doses of psilocybin decrease task-dependent creativity (convergent thinking and divergent fluency), while seven days after treatment the number of novel ideas increased. Fortunately, novel opportunities to study cognitive enhancement via psychedelics arose recently.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations